The expansion of Frontex: Symbolic measures and long-term changes in EU border management - Raphael Bossong (Stiftung Wissenschaft und Politik (SWP), 2019)
Strengthening external border management remains the lowest common denominator among Member States of the European Union (EU). Plans to expand the European Border and Coastguard Agency (Frontex) were formally adopted at the beginning of November. However, they will do little to meet the most pressing challenges of the EU's migration policy. The goal of placing 10,000 border guards under the command of Frontex can only be achieved in the medium term. While some EU Member States currently use illegal practices to secure their national borders, Frontex is increasingly subject to legal controls; operational missions are only possible by invitation from the country of deployment. Without violating legal principles, Frontex alone will not be able to accelerate the return of those who are the subject of removal orders from the EU. Nevertheless, the forthcoming Frontex reform will provide some additional technical value for securing the EU's external borders. Under changed political circumstances, the agency may be a pioneer for more European and operational security cooperation.
Keywords: 320